PENERAPAN MODEL MOVING CLASS TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI - Mira Bella; Fitri Oviyanti; Muhammad Fauzi (PAI RAFAH, 2019)
This research was motivated by the rapid progress of schools in this modern era, every school carries out new innovations, one of which is using a moving class model that can help teachers to improve student learning motivation and improve the quality of the learning. The problems in this study are: (1) How students' learning motivation does not apply the moving class model on Class VII Islamic Education subjects in SMP Negeri 1 Pampangan, (2) How is student motivation applied to the moving class model on the subjects of VII Islamic Education SMP Negeri 1 Pampangan, (3) Is there an influence of the application of the moving class model on student learning motivation in Class VII Islamic Education Subjects in SMP Negeri 1 Pampangan.The research design used is a quantitative technique using the true experimental design method with the form of post-test only control design. This research was conducted in State Junior High Schools 1 in the 2018/2019 academic year. The subjects in this study were students of class VII.3 (control) and class VII.5 (experiment) with a total of 60 students. The object in this study is student learning motivation by applying the moving class model. Data collection techniques used were questionnaires and observations. The data analysis technique used is the t-test.The results of this study indicate that the results of the analysis of the t-test values ​​obtained tcount> ttable or 6.17> 1.67 at the significance level of 5%. Then H0 is rejected, which means that there is an effect of the application of the moving class model on learning motivation in the subjects of class VII Islamic Education in SMP Negeri 1 Pampangan. This is also evident from the participation of students who are active when the learning process takes place.